Cerebral tomoelastography based on multifrequency MR elastography in two and three dimensions - Herthum, Helge; Hetzer, Stefan; Kreft, Bernhard; Tzschätzsch, Heiko; Shahryari, Mehrgan; Meyer, Tom; Görner, Steffen; Neubauer, Hennes; Guo, Jing; Braun, Jürgen; Sack, Ingolf (Frontiers in Bioengineering and Biotechnology, 2022)
Purpose: Magnetic resonance elastography (MRE) generates quantitative maps of the mechanical properties of biological soft tissues. However, published values obtained by brain MRE vary largely and lack detail resolution, due to either true biological effects or technical challenges. We here introduce cerebral tomoelastography in two and three dimensions for improved data consistency and detail resolution while considering aging, brain parenchymal fraction (BPF), systolic blood pressure, and body mass index (BMI). Methods: Multifrequency MRE with 2D- and 3D-tomoelastography postprocessing was applied to the brains of 31 volunteers (age range: 22 – 61 years) for analyzing the coefficient of variation (CV) and effects of biological factors. Eleven volunteers were rescanned after one day and one year to determine intraclass correlation coefficient (ICC) and identify possible long-term changes. Results: White matter shear wave speed (SWS) was slightly higher in 2D-MRE (1.28 ± 0.02 m/s) than 3D-MRE (1.22 ± 0.05 m/s, p<0.0001), with less variation after one day in 2D (0.33 ± 0.32%) than in 3D (0.96 ± 0.66%, p=0.004), which was also reflected in a slightly lower CV and higher ICC in 2D (1.84%, 0.97 [0.88 - 0.99]) than in 3D (3.89%, 0.95 [0.76 - 0.99]). Remarkably, 3D-MRE was sensitive to a decrease in white matter SWS within only one year, whereas no change in white matter volume was observed during this follow-up period. Across volunteers, stiffness correlated with age and BPF, but not with blood pressure and BMI. Conclusions: Cerebral tomoelastography provides high-resolution viscoelasticity maps with excellent consistency. Brain MRE in 2D shows less variation across volunteers in shorter scan times than 3D-MRE, while 3D-MRE appears to be more sensitive to subtle biological effects such as aging.